Laboratory Experiment and Numerical Analysis on the Precursory Hydraulic Process of Rainfall-Induced Slope Failure - Joon-Young Park; Young-Suk Song (Advances in Civil Engineering)
A combined analysis involving a laboratory test and numerical modeling was performed to investigate the hydraulic processes leading to slope failure during rainfall. Through a laboratory landslide test in which artificial rainfall was applied to a homogeneous sandy slope, the timing and configurations of multiple slides were identified. In addition, volumetric water content was measured in real time through the use of monitoring sensors. The measured volumetric water content data were then used to validate the relevance of the numerical modeling results. The validated numerical modeling of the laboratory-scale slope failures provided insight into the hydraulic conditions that trigger landslides. According to the numerical modeling results, the miniaturized slope in the laboratory test was saturated in a manner so that the wetting front initially progresses downward and then the accumulated rainwater at the toe of the slope creates a water table that advances toward the crest. Furthermore, each of the five sequential failures that occurred during this experiment created slip surfaces where the pore-water pressure had achieved full saturation and an excessive pore-water pressure state. The findings of this study are expected to help understand the hydraulic prerequisites of landslide phenomena.